2009
DOI: 10.1038/gt.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Widespread biochemical correction of murine mucopolysaccharidosis type VII pathology by liver hydrodynamic plasmid delivery

Abstract: Mucopolysaccharidosis type VII (MPS VII) is a lysosomal storage disease caused by a deficiency of the acid hydrolase b-glucuronidase. MPS VII mice develop progressive lysosomal accumulation of glycosaminoglycans (GAGs) within multiple organs, including the brain. Using this animal model, we compared two plasmid gene administration techniques: muscle electrotransfer and liver-directed transfer using hydrodynamic injection. We have evaluated both the expression kinetics and the biodistribution of b-glucuronidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…New formulations of the molecules could also enable an increase in the circulating level and/or half-life of the compounds. Finally, the proposed substrate deprivation therapy could be used in combination with other therapeutic strategies restoring enzyme activity, such as nonviral liver-directed gene therapy (Richard et al 2009), which has demonstrated a significant biochemical and histological correction both in peripheral organs and in the CNS of MPS VII mice.…”
Section: Discussionmentioning
confidence: 98%
“…New formulations of the molecules could also enable an increase in the circulating level and/or half-life of the compounds. Finally, the proposed substrate deprivation therapy could be used in combination with other therapeutic strategies restoring enzyme activity, such as nonviral liver-directed gene therapy (Richard et al 2009), which has demonstrated a significant biochemical and histological correction both in peripheral organs and in the CNS of MPS VII mice.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of the results obtained on MPS VII mice by our group (Richard et al, 2009, the beneficial effect of gene transduction into the liver or other peripheral tissues is generally considered to be restricted to peripheral organs, as the secreted enzyme will not cross the blood brain barrier. Therefore, vector delivery systems have been developed for direct in vivo gene transfer into the CNS.…”
Section: In Vivo Gene Therapymentioning
confidence: 83%
“…Non viral methods were also tested by our group to target the liver of MPS VII mice, using hydrodynamic injections of plasmid containing the beta-glucuronidase cDNA, leading to improvements in both peripheral and brain manifestations of MPS VII disease (Richard et al, 2009). The surprising biochemical correction observed in brain, while only the liver was producing the enzymes in this particular study, points to the possibility of the therapeutic enzymes crossing the blood-brain barrier (BBB) when continuously produced at the periphery.…”
Section: In Vivo Gene Therapymentioning
confidence: 99%
“…in muscle, greater secretion and therapeutic results have frequently been obtained after relatively similar transduction of other tissues more suited for these tasks, such as liver [204]. This suggests that ways to improve the processing and release of molecules from muscle are needed.…”
Section: Optimising the Transgene: Engineering The Insulin Gene And Pmentioning
confidence: 98%